PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP MINAT DAN HASIL BELAJAR IPS PADA SISWA KELAS V SD NEGERI 291 MALUKU TENGAH - Olga Aprillia Sipahelut; Leonid Ritiauw; Fadhilah Hukmiah (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The low level of student instructional attention due to the application of a passive, teacher-centered teaching model is the background of this research activity. These operational problems trigger acute boredom, minimal emotional involvement, and a shallow understanding of social science material daily in the classroom. The main focus of this scientific study is to analyze the magnitude of the influence of the problem-based learning (PBL) model on the escalation of interest and learning outcomes of fourth-grade students in social studies. The steps of the quasi-experimental quantitative approach with a one-group pretest-posttest design were operated using a total sample of 20 respondents at SD Negeri 291 Central Maluku. The data collection procedure was collected in a structured manner via a four-level Likert scale questionnaire instrument and an essay-shaped evaluation test, which was then executed statistically using the Shapiro-Wilk residual normality test, paired sample t-test hypothesis testing, and N-gain value calculation. Quantitative data empirically revealed a significant increase in learning interest with a significance level of 0.000 and a high N-gain score of 0.7693. Students' cognitive learning outcomes also skyrocketed, with a significance value of 0.000 and an N-gain index of 0.7451. The main conclusion confirms that digitalization of local contextual problem-solving has proven highly effective in boosting students' academic resilience and critical thinking independence. ABSTRAK Rendahnya atensi instruksional siswa akibat pengaplikasian model pengajaran pasif yang berpusat pada guru melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu kejenuhan akut, minimnya keterlibatan emosional, serta pemahaman materi ilmu sosial yang bersifat dangkal harian di dalam kelas. Fokus utama kajian ilmiah ini adalah menganalisis besaran pengaruh model problem-based learning (PBL) terhadap eskalasi minat dan hasil belajar IPS siswa kelas empat. Langkah-langkah pendekatan kuantitatif kuasi eksperimen dengan desain one group pretest-posttest design ini dioperasikan menggunakan sampel total sebanyak 20 responden di SD Negeri 291 Maluku Tengah. Prosedur pengumpulan data dikumpulkan secara terstruktur via instrumen angket kuesioner skala Likert empat tingkat dan tes evaluasi berbentuk esai (essay), yang selanjutnya dieksekusi statistik menggunakan uji normalitas residual Shapiro-Wilk, pengujian hipotesis paired sample t-test, dan perhitungan nilai N-gain. Data kuantitatif secara empiris menyingkap peningkatan signifikan pada minat belajar dengan angka signifikansi 0,000 serta skor N-gain tinggi sebesar 0,7693. Hasil pencapaian belajar kognitif siswa juga melesat tajam dengan nilai signifikansi 0,000 dan capaian indeks N-gain sebesar 0,7451. Simpulan utama menegaskan bahwa digitalisasi pengondisian masalah kontekstual lokal terbukti sangat andal dalam mendongkrak ketahanan akademik serta kemandirian berpikir kritis siswa.